Competency-Based Training and Self-Efficacy on Work Readiness Through Employability Skills in The Center for Vocational Training and Productivity and Productivity - Urrofik, Safira Arbella Aurell; Arbarini, Mintarsih; Suminar, Tri; Cahyani, Arini Dwi (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Current technological developments have created new needs for professional workers. However, the availability of workers currently does not meet the criteria of professional workers, causing unemployment rates to increase. The purpose of this study was to analyze the direct effect of competency-based training and self-efficacy on work skills; the direct effect of competency-based training, self-efficacy, and work skills on work readiness; and the indirect effect of competency-based training and self-efficacy on work readiness through work skills. This study uses a quantitative approach with the ex post facto method. The sample in this study was 367 people who were training participants at the Semarang City Vocational Training and Productivity Center. The data collection method uses a closed questionnaire method. The data analysis technique uses the path analysis method. The results of the study showed that competency-based training and self-efficacy had an effect on work skills. The same thing was also shown that competency-based training, self-efficacy, and work skills had an effect on work readiness. Meanwhile, the indirect effect of competency-based training and self-efficacy on work readiness through work skills also showed significant or influential results. The conclusion obtained is that the variables of competency-based training, self-efficacy, work skills, and work readiness show a significant influence between variables. Thus, the four variables can create good work readiness and can compete as professional workers.